Agricultural Health and Safety: Evaluating Farmers’ Knowledge, Attitude, and Safety Behavior in Northern Thailand - Anurak Wongta; Nootchakarn Sawarng; Phannika Tongchai; Pichamon Yana; Surat Hongsibsong (Safety and Health at Work)
Background: Agriculture is vital for economic growth and livelihoods in northern Thailand, yet it is challenged by hazardous practices such as improper chemical use and machinery accidents. This study aimed to evaluate the risk and determine the relationship between pesticide exposure and knowledge, attitudes, and safety behaviors. Methods: This cross-sectional study was conducted between October and December 2017 in the San Pa Tong district of Chiang Mai, Thailand. Data were collected through structured questionnaires and face-to-face interviews with 280 farmers. Results: The findings indicated that knowledge and safety behavior scores varied significantly with educational attainment and training received. Farmers with higher education levels or those who had undergone training exhibited better knowledge and safer behavioral practices, whereas income levels did not significantly affect knowledge or safety behaviors. The pesticide exposure risk level was associated with the study variables, with those recognizing a ‘normal’ risk level demonstrating greater knowledge and safer behaviors than those who reported the risk level as safe or at risk. A strong positive correlation between knowledge and safety behavior was observed, indicating that increased awareness can result in more cautious practices. These findings suggest that educational and training programs are crucial for promoting safer pesticide use among farmers. Although attitudes toward pesticide safety varied based on income, education, and training positively influenced knowledge and behavior. Conclusion: The study concludes that understanding farmers’ perceptions of pesticide risks is essential for designing and implementing effective educational interventions.